Comprehensive textbook of sexual medicine - Kar, Nilamadhab; Kar, Gopal Chandra (Jaypee Brothers Medical Pub., 2014)
It covers almost all areas relevant in the study of sex besides disorders, developmental aspects and cultural, psychological, social and legal issues which are important for sound clinical practice.